2006
DOI: 10.1007/s10552-005-0539-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival Among Patients with Adenocarcinoma of the Pancreas: A Population-based Study (United States)

Abstract: This study is the largest population-based study to date to explore survival from pancreatic cancer among all age groups in a racially diverse population. Median survival was shorter than that reported from other series. Race/ethnicity did not have a significant effect on survival. However patients residing in poor neighborhoods were less likely to undergo resection and somewhat less likely to survive this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
126
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 20 publications
16
126
4
3
Order By: Relevance
“…However, a small but statistically significant decrease in the proportion of cases refusing treatment by SES quintile was noted for surgery, radiation therapy, and chemotherapy. In a smaller study of CCR data from 1994 to 2000, other investigators have reported that SES (as a dichotomized variable) was not significantly associated with survival among pancreatic adenocarcinoma cases on adjusted analysis (18). However, cases with low SES were noted to be less likely to receive surgical treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a small but statistically significant decrease in the proportion of cases refusing treatment by SES quintile was noted for surgery, radiation therapy, and chemotherapy. In a smaller study of CCR data from 1994 to 2000, other investigators have reported that SES (as a dichotomized variable) was not significantly associated with survival among pancreatic adenocarcinoma cases on adjusted analysis (18). However, cases with low SES were noted to be less likely to receive surgical treatment.…”
Section: Discussionmentioning
confidence: 94%
“…However, cases with low SES were noted to be less likely to receive surgical treatment. Effect modification to address the interaction of SES and treatment variables on survival of African-American cases was not done in that study, and the investigators comment in their discussion that further research is needed to explore apparent treatment disparities (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of early diagnosis and high incidence of metastatic disease at initial diagnosis, only 15-20% of patients are resectable. [2][3][4] Even so, the 5 y survival rate among those radically operated patients is only about 5-20%. 2,5,6 To date, chemotherapy still remains the most important adjuvant therapy in patients with pancreatic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from New England, for example, showed that a higher SES is significantly associated with improved overall survival following pancreatic cancer resection [5], thereby indicating a relationship between SES and the quality of care delivered and outcomes. One of the largest population-based studies on pancreatic cancer survival, conducted in California, showed that poorer patients were less likely to undergo resection and less likely to survive this malignancy and that median survival increased with SES [6]. Accordingly, Zell et al reported a poorer pancreatic cancer survival for underprivileged minorities with lower SES due to treatment differences [7].…”
Section: Introductionmentioning
confidence: 99%